Regulation of Coaching Patterns for Women Narcotics Prisoners (Study in Class II A Medan Women's Prison) - Simanjuntak, Alberto Dober (International Journal Labs, 2023)
This study aims to describe the regulation of coaching patterns for women narcotics prisoners in Class II A Correctional Institution Medan City and explain the rights of female prisoners in drug cases based on Law No.12 of 1995 jo Law No.22 of 2022 concerning corrections. Then explained the implementation of Law No. 35 of 2009 article 54 concerning the rehabilitation of female prisoners in Medan's Class II A Community Institution. This study uses qualitative descriptive design with sources of legal materials Laws and regulations. Koba. Data collection techniques in this study used in-depth interviews and observations. The results of this study found that the regulation of the pattern of coaching female prisoners in Tanjung Gusta Medan Class IIA Prison has been running quite well and the Rights of Women Prisoners have been running based on the applicable Law and the Implementation of Law No. 35 of 2009 article 54 concerning rehabilitation of residents assisted by drug cases in Class II A Medan Women's Prison can be frogated